Ação da angiotensina II central sobre o balanço térmico e o desempenho físico - Rafael Silva Valle de Almeida (2012)
The aim of this study was to investigate the effects of increased central nervous system availability of angiotensin II (ANG II) over exercise performance and the relationship between the thermal balance and determination of fatigue in untrained rats subjected to physical exercise. Wistar rats weighing between 250 and 350g. The animals were implanted with a guide cannula in the right lateral ventricle for administration of ANGII by intracerebroventricular injection (icv) at doses of 0,25 µg, 1 µg , 2 µg e 4 µg or Saline (n = 8). The animals spent at least 3 experimental situations. The internal body temperature (Tb) was determined by telemetry via temperature sensor implanted in the animal's intraperitoneal cavity. The tail temperature (Ttail) was measured using a temperature sensor attached to the animal's tail. Both temperatures were measured continuously while the animals performed a submaximal exercise in a rodent metabolic treadmill, at a speed of 18m/min and 5% inclination, until failure. The results showed that the central availability of ANG II induced a dose-response curve with an inverted U shape. There was a positive relationship between the increasing dose of ANG II and physical performance observed up to a dose of 2 µg. However a negative relationship was observed between the dose of 4 µg and physical performance. From the data obtained were calculated: body heat storage (BHR), heat storage rate (HSR), body temperature threshold for vasodilation (TTbV), exercise time (ET) and work (W). The icv administration of ANG II 2 µg induced an increase in ET (Salina: 16.95 ± 1.9 min vs. ANG II 2 µg: 27.32 ± 0.28 min, p <0.05) and W (Salina: 5,22 ± 0.47 vs. ANG II 2g Kgm: 8.18 ± 0.47 Kgm, p <0.05) compared to the control group. The icv administration of ANG II 4 µg caused significant reductions in ET (Salina: 16.95 ± 1.9 min vs. ANG II 4g: 10.24 ± 1.49 min, p <0.05) and W (Salina: 5, 22 ± 0.47 vs. ANG II 4g Kgm: 2.26 ± 0.38 Kgm, p <0.05) compared to the control group. This reduction is related to the significant increase shown in the BHR (Saline: 0.03 ± 0.01 ° C / min vs. Ang II 4g: 0.07 ± 0.01 ° C / min, p <0.05), HSR ( Salina: 8.67 ± 0.93 cal / min vs ANG II 4g: 21.16 ± 1.06 cal / min, p <0.05), TTbV (Salina: 37.85 ± 0.03 ° C vs ANG 4g II: 38.28 ± 0.04 ° C, p <0.05) and higher elevation in Tb compared to the control group. These results suggest that the availability central ANG II causes distinct effects during exercise depending on the administered dose, assuming a behavior of inverted U-shaped curve. In intermediate doses causes an increase in performance demonstrated by increased time to fatigue, possibly related to other factors besides the central thermoregulation. At high doses, the central ANG II causes a reduction in performance related to the sharp increase in Tb, BHR, HSR and TTbV, but without changes in Ttail, indicating that these changes are related to the increase in heat produced during exercise.